The environment and kidney health: challenges and opportunities - Joyita Bharati; Carol Zavaleta-Cortijo; Tiana Bressan; Aakash Shingada; Gregorio Obrador; Laura Sola; David Peiris; J Jaime Miranda; Vivekanand Jha (Instituto Nacional de Salud Pública, 2022)
The accelerating environmental degradation as a result of modernisation and climate change is an urgent threat to human health. Environment change can impact kidney health in a variety of ways such as water scarcity, global heating and changing biodiversity. Ever increasing industrialization of health care has a large carbon footprint, with dialysis being a major contributor. There have been calls for all stakeholders to adopt a 'one health approach' and develop mitigation and adaptation strategies to combat this challenge. Because of its exquisite sensitivity to various elements of environment change, kidney health can be a risk marker and a therapeutic target for such interventions. In this narrative review, we discuss the various mechanisms through which environmental change is linked to kidney health and the ways that the global kidney health communities can respond to environmental change.